Perception of Trainers for the Athlete - Nuri Berk Güngör; Serkan Kurtipek (Selcuk University, 2019)
ABSTRACTThe aim of this research is to determine the perceptions of the trainers in different sports branches on the athletes through metaphors. The sample of study consists of 72 trainers in different sports branches. For the collection of data in the study, "metaphor form" was prepared to determine the participants' views on the concept of athletes. In the metaphor form, the athletes were asked to complete the sentence of "Athlete is like...; Because ..." In this study, phenomenological design from qualitative research approaches is used. In the analysis of the data, content analysis technique was used. For the reliability of the analysis of the research data, the reliability coefficient was calculated between the participants and this value was found to be 93%. With the evaluation of the data, it was seen that the sports club members produced 32 metaphors. These metaphors were collected in 4 different categories. While the trainers were determined to develop metaphors most in the category of "openness to development" and "value" for the concept of athlete, these categories were followed by categories of "responsibility" and "being hardworking". The most produced metaphors of the trainers are diamond, baby, sapling, bee, rough mine and gold. Trainers often used live and tangible metaphors for the concept of athlete.